Peran Akuntansi Digital dalam Meningkatkan Ketepatan, Transparansi dan Efisiensi Laporan Keuangan pada UMKM - Nurvadillah, Nurvadillah; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of digital accounting in improving the accuracy, transparency, and efficiency of financial reporting within Micro, Small, and Medium Enterprises in the digital economy era. The research employed a qualitative non empirical approach based on library research through the synthesis of academic literature related to accounting digitalization, financial governance, and technological transformation in MSMEs. The findings indicate that digital accounting strengthens financial reporting quality through integrated accounting information systems, improved auditability, and more adaptive financial monitoring mechanisms. The study also identifies several structural challenges, including limited digital literacy, technological infrastructure constraints, organizational resistance, and unequal human resource readiness among MSMEs. These findings demonstrate that the sustainability of digital accounting transformation depends on technological adoption, institutional readiness, and continuous capacity development in strengthening financial governance and business sustainability.